2016
DOI: 10.1515/pomr-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Heating Control of Heated Twin Radiosonde Humidity Sensor Based on DMC

Abstract: In order to effectively solve condensation and icing problems of radiosonde in low-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…At the same time, the form of BCR2 was manganese oxide, which greatly reduced biological efficacy and provided the guarantee for the safe treatment of copper after biological iron sulfide composites removing copper. Many articles reported that SRB had a vertical distribution in sediments of 12-24 cm where bacterial abundances in general and SRB abundances in particular were both maximal; therefore, depth might also be the main reason that affects the heavy metal removal rate of SRB (Jiang et al 2009, Varon-Lopez et al 2014, Sun et al 2016, de Oliveira et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the form of BCR2 was manganese oxide, which greatly reduced biological efficacy and provided the guarantee for the safe treatment of copper after biological iron sulfide composites removing copper. Many articles reported that SRB had a vertical distribution in sediments of 12-24 cm where bacterial abundances in general and SRB abundances in particular were both maximal; therefore, depth might also be the main reason that affects the heavy metal removal rate of SRB (Jiang et al 2009, Varon-Lopez et al 2014, Sun et al 2016, de Oliveira et al 2016.…”
Section: Discussionmentioning
confidence: 99%